2022
DOI: 10.1007/s00592-022-01943-7
|View full text |Cite|
|
Sign up to set email alerts
|

Association of glucose-lowering drugs with incident stroke and transient ischaemic attacks in primary care patients with type 2 diabetes: disease analyzer database

Abstract: Aims Previous observational studies on glucose-lowering drugs and risk of stroke in type 2 diabetes yielded conflicting results. The aim was to examine the association of glucose-lowering drugs with incident stroke and transient ischaemic attacks (TIA) in newly diagnosed type 2 diabetes. Methods We conducted a retrospective cohort analysis of the disease analyzer, which comprises a representative panel of 1248 general and internal medicine practices throug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…Since the range of variation in body height in a given population is usually small, a large number of events is required for reliable risk assessment. The IQVIA DA database used for the analyses in this study has already been validated by several studies [ 23 ] and previously used in studies on body height [ 24 , 25 ] and diabetes mellitus [ 26 , 27 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the range of variation in body height in a given population is usually small, a large number of events is required for reliable risk assessment. The IQVIA DA database used for the analyses in this study has already been validated by several studies [ 23 ] and previously used in studies on body height [ 24 , 25 ] and diabetes mellitus [ 26 , 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Data are anonymously transferred to IQVIA on a regular basis, and the quality of these data is assessed using several criteria, such as completeness of documentation and linkage between diagnoses and prescriptions. The DA database has been shown to be representative for general and specialized practices in Germany [ 23 ] and was previously published in several studies focusing on body height [ 24 , 25 ] as well as diabetes mellitus [ 26 , 27 ].…”
Section: Methodsmentioning
confidence: 99%
“…It appears that our findings differ because the included article in our study compared MET combination therapy with MET + SU, rather than directly contrasting it with MET monotherapy. Otherwise, the American Diabetes Association and the European Association for the Study of Diabetes [ 79 ] recommend SGLT2-i or GLP-1RA as hypoglycemic agents for patients at high risk of cardiovascular disease, and studies [ 11 ] have shown that SGLT2-i or GLP-1RA may reduce the risk of stroke in patients with T2DM. Nonetheless, given the limited number of articles included, there is not adequate evidence to conclusively support these findings.…”
Section: Disscussionmentioning
confidence: 99%
“…Recent studies indicate a predictive relationship between T2DM microvascular complications such as diabetic nephropathy (DN), DR, diabetic neuropathy, and the likelihood of stroke [ 10 ]. Furthermore, emerging evidence recognizes the cardiovascular protective properties of novel hypoglycemic drugs like sodium-glucose cotransporter-2 inhibitors (SGLT-2is) and glucagon-like peptide-1 receptor agonists (GLP-1 RAs) [ 11 ]. However, the existing body of research on stroke causation in T2DM patients exhibits variations in focus, population demographics, sample sizes, and consequent disparate findings.…”
Section: Introductionmentioning
confidence: 99%
“…Data from real-world studies showed significant risk reductions for stroke with SGLT2 inhibitor use. [3][4][5] That said, some of these studies did not distinguish ischaemic strokes from the other stroke subtypes and a meta-analysis of randomized controlled trials on stroke subtypes suggests that a protective effect from SGLT2 inhibitors is only observed for haemorrhagic strokes. 6 Further studies are required to determine the association between SGLT2 inhibitors and ischaemic strokes, in view of the conflicting results.…”
mentioning
confidence: 99%